Economic Integration, Imperfect Competition, and International Policy Coordination - Bertil Holmlund; Ann-Sofie Kolm (Uppsala University, Department of Economics, 1999)
The paper examines policy externalities between imperfectly competitive open economies where unemployment prevails in general equilibrium. We develop a two-country and two-sector model with monopolistic competition in the goods market and wage bargaining in the labor market. Policy externalities operate through the real exchange rate and economic integration is modeled as a reduction in trade costs. We explore how market integration influences policy spillovers, employment and real wages. We also examine how national and supranational commodity tax policies affect sectoral and total employment. Finally, we characterize optimal commodity taxes with non-cooperative and cooperative policies and offer some rough estimates of the welfare gains from policy coordination, using a calibrated version of the model.
urn:nbn:se:uu:diva-2446
Keywords: D43; E61; F15; J23; J64; 330; Economic integration; imperfect competition; wage determination; policy cooperation; Wirtschaftsintegration; Unvollkommener Wettbewerb; Offene Volkswirtschaft; Zwei-Länder-Modell; Monopolistischer Wettbewerb; Handelbare Güter; Nicht-handelbare Güter; Verbrauchsteuer; Allgemeines Gleichgewicht; Theorie